A head-neck biomechanical model of a 6-year-old child for frontal crash studies. (20th April 2010) - Cazon, Aitor; Suescun, Angel
The objective of this research is the development of a detailed computational model describing the kinematic and dynamic behaviour of a 6-year-old child head-neck group in frontal crash situations without head contact. The child model was scaled down from a previous biomechanical adult head-neck group. Three validation processes were performed. Firstly, the head centre of gravity acceleration was validated against the response of the head-neck group of MADYMO® Hybrid III 6-year-old dummy during a frontal crash. Secondly, the head centre of gravity displacement was validated against the scaled response of adult volunteers during a frontal crash. Finally, the occipital condylar moment was compared against the biofidelity requirements for Hybrid III 6-year-old dummy during the pendulum calibration test. Results showed good correlation between the response of the child model and both validation subjects, the child dummy and the scaled response of adult volunteers.